Factors Affecting Employee Performance: An Investigation on Private School Sector - Aisha Yusuf Mesiya (Institute of Business Management, 2019)
mployees are valuable assets for any organization, and their productivity should be given due consideration, if an organization aims to meet its strategic goals. This can be done through implementation of effective policies for the most contributing determinants of performance of employees. Therefore, this paper studies the factors that affect employee performance significantly, and gauges their direction being positive or negative. The study is based on the case of education sector, specifically the private schools of Pakistan. The sample is drawn from private schools of Karachi, with respondents selected through Convenience Sampling. A qualitative design with Interpretivist approach and case study research strategy is used and 30 employees at Top, Middle and Lower job levels of schools have been interviewed. The instrument used for collecting the data comprises of semi-structured interview questions, the data then organized, coded and developed into themes for conducting the analysis. From our framework of ten factors, compensation, motivation, leadership, working environment, performance appraisal, job experience, and training are found to have significant and positive impact on work performance, while conflict, job stress, and working hours bear significant negative effect on employee work performance. These factors have varied level of impact through the three job levels. In addition to the established framework, eleven new factors were also identified while conducting the interviews and their effect through each employment level was gauged. Conclusively, several recommendations are drawn for the organizations to ensure maximum effectiveness and efficiency of their employees.